A thematic study on sports and physical fitness in the light of the sunnah - Muhammad Fawwaz bin Muhammad Yusoff (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
The focus of this study aims at gathering the aḥadith dealing with sports and examine them in order to review the subject from the Sunnah perspective. It covers and discusses these elements: the concept of sport, types: Sports in the era of Prophet PBUH, ancient and modern sports, a purposeful interpretation reading the ḥadith to legalizes sports, and a guidelines to athletes and spectators who involve in sports. The researcher used inductive method, through tracing the aḥadith that have relation to sports, and then, referring back to the commentary aḥadith books, as well as to the books that have basis relation. The researcher also used analytical and deductive method in examining the aḥādīth of the Messenger . Hence, identify authentic aḥadith and relate what constitute as being guidelines in the domain of sports.